Effect of Walnut Tea and Microcapsule Saturated with Lavender Oil on Vase Life of Gerbera Flowers - Güzella Yılmaz; Hakan Karadağ (Turkish Journal of Agriculture: Food Science and Technology)
In the study, it was aimed to increase the vase life of Basic, Ulaş and Terra Ozan cultivars of Gerbera sp. For this purpose, microcapsules containing lavender oil (1000 and 1500 ppm) and naturally obtained walnut tea (33% and 50%) were used. Sucrose (4%) was added to all vase solutions, including the control group solutions. The experiment was set up with 3 replications (three vases) for each treatment and one flower per replication. As a result of the experiment, it was observed that both walnut tea and lavender treatments did not cause a significant change in the vase life of the Terra Ozan cultivars. In the Basic cultivar, the vase life of the flowers in the solution containing lavender oil was longer than that in the solution containing walnut tea, but both treatments did not make a significant difference compared to the control. In Ulaş, both walnut tea and lavender oil applications caused significant increases in the vase life of the flowers. The applications made in the study caused significant changes in the water intake of the flower stems. The treatments that increase the water intake also increased the vase life.